Construction of Religious Identity in Pakpak Culture Community in Dairi District - Maimanah Angkat; Katimin Katimin; Anwarsyah Nur (Budapest International Research and Critics University, 2019)
the aims of the study is to find out the construction of religious identity in pakpak culture community in Dairi district. The result of the study shows that there are three variations of dependence of Pakpak religion / belief and culture acculturation on other religions and cultures, the first group, traditional groups, in this group Pakpak's identity is still maintained and is dominated by parents and village communities who live far from pluralism occupation culture. Second, the bicultural group, this group is dominated by the Pakpak people who live in urban areas and who have received an established education, the behavior of this group is still thick with its Pakpak identity but has accepted differences with other religions and cultures. The three modern groups, in this group are dominated by Pakpak people who have long migrated to other areas and their Pakpak identity has changed. Of these three groups, the level of open personality was found to be very prominent for adolescents who became embryos of the development of Pakpak culture, such as the formation of identity, and interacting with peers.